Master's recital and program notes - Lowen, Richard Allen. (My University, 1975)
The 17th century solo cantata was influenced by the stylistic and formal developments of the opera of that period. Stylistically, bel canto elements introduced in the opera are reflected in the simple, melodic vocal line of the cantata. Formally, the cantata assumes the alternation of clearly defined sections of recitative and aria, another direct influence of the opera. The cantata soon took the place of the madrigal as the most popular form of vocal chamber music. Eventually this popularity offered a valuable training ground for operatic composers. Experiments with new formal, melodic, and harmonic features appeared first in cantatas before being transferred to operatic arias and recitatives.
Call number: LD2668 .R4 1975 L69
Keywords: Songs (High voice) with piano.; Masters theses